2006
DOI: 10.1520/gtj12129
|View full text |Cite
|
Sign up to set email alerts
|

New and Economical Mixing Method of Cement-Admixed Clay for DMM Application

Abstract: The results of unconfined compression and oedometer compression tests confirmed the existence of optimum mixing clay water content for economical and efficient mixing of cement and clay for deep mixing method (DMM) application. A concept supporting the existence of optimum mixing clay water content is presented, and a schematic diagram idealizing the clay-water-air-cement interactions is illustrated. The optimum mixing clay water content (Cw,opt) is defined as the total clay water content of the clay-water-cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In extreme conditions of high water contents, a high after-curing void ratio occurs, while in extreme conditions of low water contents, uneven mixing occurs. Lorenzo et al confirmed the existence of an optimum moisture content for mixing clay: about 1.10 times base clay's LL [49]. However, the addition of cement to cement-treated clay leads to an increase in the LL of the clay.…”
Section: Liquid Limit and Flow Valuementioning
confidence: 97%
“…In extreme conditions of high water contents, a high after-curing void ratio occurs, while in extreme conditions of low water contents, uneven mixing occurs. Lorenzo et al confirmed the existence of an optimum moisture content for mixing clay: about 1.10 times base clay's LL [49]. However, the addition of cement to cement-treated clay leads to an increase in the LL of the clay.…”
Section: Liquid Limit and Flow Valuementioning
confidence: 97%
“…Portland Cement (PC) is created in a controlled chemical process with the combination of aluminum, calcium, iron, silicon, and other compounds. In order to construct Blended Portland Cement (BPC), an amount of gypsum, and several minerals are mixed with PC or clinker in the hydraulic adhesive process [3,4].…”
Section: Investigation Of the Reaction In Soil Cement Columnsmentioning
confidence: 99%
“…In these terminologies, the Deep Soil Mixing (DSM) has certain advantages such as: rapid stabilization, accelerated construction in site, higher soil strength at lower cost. Authors in [3][4][5] showed that DSM is suitable for application in some problematic soils, especially expansive soils. Typical DSM has been applied in reclaimed and soft native soils in the transportation sector in Japan [6].…”
Section: Introductionmentioning
confidence: 99%